1996
DOI: 10.1007/bf01806210
|View full text |Cite
|
Sign up to set email alerts
|

A prothrombotic state in breast cancer patients treated with adjuvant chemotherapy

Abstract: Cancer is often associated with abnormal activation of coagulation leading to a prothrombotic state. Some chemotherapeutic agents used for cancer may induce thrombosis but their biological alterations in the hemostatic system are not yet well understood. This study evaluated alterations of coagulative and fibrinolytic parameters following chemotherapy. In plasma samples of 38 patients (median age: 49 years) receiving CMF (schedule 1-21 or 1-8) for Stage II breast cancer, we evaluated: PT, aPTT, antithrombin II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
6
30
0
2
Order By: Relevance
“…The almost universal, significant response of the measured molecules to breast cancer chemotherapy demonstrates that chemotherapy has a significant effect on coagulation and supports previous studies (Canobbio et al, 1986;Rogers et al, 1988;Feffer et al, 1989;Rella et al, 1996;Pectasides et al, 1999).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The almost universal, significant response of the measured molecules to breast cancer chemotherapy demonstrates that chemotherapy has a significant effect on coagulation and supports previous studies (Canobbio et al, 1986;Rogers et al, 1988;Feffer et al, 1989;Rella et al, 1996;Pectasides et al, 1999).…”
Section: Discussionsupporting
confidence: 88%
“…Several small studies have reported alterations in markers of coagulation in response to breast cancer chemotherapy, which support the development of a chemotherapy-induced hypercoagulable state (Canobbio et al, 1986;Rogers et al, 1988;Feffer et al, 1989;Rella et al, 1996;Pectasides et al, 1999). Several pathogenic mechanisms have been suggested such as increased expression or release of procoagulants and cytokines from damaged cells, a direct toxic effect on vascular endothelium or upregulation of platelet or monocyte activity.…”
mentioning
confidence: 89%
“…Alterations in hemostasis have been identified in breast cancer patients receiving CMF (cyclophosphamide, methotrexate and fluorouracil) and have been evaluated employing coagulative and fibrinolytic parameters such as prothrombin time (PT), antithrombin III (AT III), thrombinantithrombin III complex, fibrinogen, tissue-type plasminogen activator (t-PA), etc. 89 In an attempt to explain these events, a recent report about CMF-chemotherapy effects on the clotting system suggests a potential interaction of these drugs with the synthesis and activation of vitamin K-dependent coagulation factors inducing abnormalities in hemostasis. 75 Increased attention has been given to the risk of venous thromboembolism following hormonal therapy, most notably the use of tamoxifen in breast cancer adjuvant treatment.…”
Section: Hypercoagulability and T Herapeutic A Gentsmentioning
confidence: 99%
“…The mortality rates of patients with calciphylaxis are high, and the main reason for death is sepsis. It is not clear how long this interval is leading death after the development of calciphylaxis (4,11). Likewise, the present patient died secondary to sepsis after one month of hospitalization.…”
Section: Discussionmentioning
confidence: 63%
“…It requires sensitization of the tissue by PTH, vitamin D, phosphate, calcium salts or renal failure. Also it needs additional challenging factors, such as iron salts, steroids and immunosuppressive drugs such as methotrexate, cylophosphamide, flourourasil (5,11,12). Steroids as challengers of calcinosis, have also been observed in renal failure patients.…”
Section: Discussionmentioning
confidence: 99%